KRIMINALISASI PEKERJA DALAM HUBUNGAN INDUSTRIAL - Abdul Malik Bram; Kaharuddin Syah (Fakultas Hukum Universitas Muhammadiyah Palu, 2020)
Criminalization often occurs in work relationships because one of the parties committed non-compliance in carrying out the contents of the work agreement in this case the employer does not pay workers' normative rights, mutates under pressure / intimidation, prohibition on organization, discrimination between female workers and male workers and actions other crimes that can harm workers. The policy in handling crime (penal policy) towards the creation of harmonization of relations between employers and workers is a concept of work relations with the model of industrial family relations based on family relations and togetherness in accordance with the philosophy of industrial relations. This paper aims to anticipate the occurrence of criminalization of employer relations with Workers requiring a norm that regulates the problem of equality before the law related to labor crimes as well as supervision and criminal law enforcement especially in the process of investigating labor criminal acts handled directly by the police. Keywords: Criminalization, Employers, and Workers